Memória, transcriação e transtextualidade em Lygia Fagundes Telles - Toledo, Naiani Borges (2019)
The research presented here was focused on reflections involving the analysis of memory and transtextualities present in Lygia Fagundes Telles’ Antes do baile verde (1970) and A disciplina do amor (1998). From studies on the subject, some questions emerged that stood out as guide for our research: How is the memory established inside the tales? Is there any way to know which tales have memories and which ones are completely fictions? What is the relation between memory and the objects responsible for triggering the recall process? And where are the transtextuality in them? With the purpose of finding answers to these questions, we outline, as a general goal, to establish a transtextual and intersemiotic analysis in the mentioned Lygia Fagundes Telles’ books. Aiming to achieve the proposed objective, we support the research in the theoretical assumptions of Bakhtin (2003), Kristeva (2005), Genette (1982), Jenny (1979), Dällenbach (1979), Perrone-Moses , Samoyault (2008), Gagnebin (2006), Santiago (1982), Bloom (1997), Lima (1986), Candido (1955), and others. It is, therefore, a research based on literature of bibliographic type, considering that its objective is to analyze tales present in the books Antes do baile verde (1970) and A disciplina do amor (1998), for it will not be made a practical field application. It also focuses on a methodological approach centered on mitochritics, phenomenology and semiotics.